The Role of Al Washliyah in Strengthening Local Wisdom Law Amid Cultural Modernization - Haidir; Muhlizar; Tri Reni Novita; M. Faisal Husna; Qori Rizqiah H Kalingga; Nurasiah Harahap; Akmal (Inovasi Pratama Internasional. Ltd, 2026)
This article examines the role of the Indonesian Islamic mass organization Al Jam’iyatul Washliyah (Al Washliyah) in strengthening local wisdom–based law (kearifan lokal) in the context of rapid cultural modernization and legal centralization in Indonesia. Drawing on a qualitative sociolegal case study, the study explores how Al Washliyah’s educational, da’wa, and social welfare programs contribute to maintaining and transforming customary norms and practices so that they continue to function as living law within communities, while also engaging with the national legal framework. The analysis situates Al Washliyah’s activities within debates on legal pluralism, adat law, and the integration of local wisdom into formal legislation. The findings indicate that Al Washliyah operates as a mediating institution between state law, Islamic law, and local customary law through three main roles: internalizing local values in Islamic education, mediating community disputes and social norms, and advocating for legal recognition of local wisdom. These roles help to reconcile cultural change with normative continuity, although tensions remain regarding formalization, generational shifts, and the commodification of culture